Wells and welfare in the Ganga Basin: public policy and private initiative in Eastern Uttar Pradesh, India - Shah, Tushaar (International Water Management Institute, 2001)
This report analyzes the history of groundwater development in the eastern Uttar Pradesh region over the 1950-1990 period. Its main conclusion is that the story of groundwater-based livelihood creation in the Ganga basin is one of failed public initiatives and successful adaptive responses by private agents. However, tube-well-induced agrarian dynamism in eastern Uttar Pradesh and north Bihar in recent years can spread to the entire basin if public policy makers learn correct lessons from the experience of these two subregions.